Incorporation of Collagen and Hyaluronic Acid to Enhance the Bioactivity of Fibrin-Based Hydrogels for Nucleus Pulposus Regeneration - Gansau, Jennifer (J Funct Biomater, 2018)
Hydrogels, such as fibrin, offer a promising delivery vehicle to introduce cells into the intervertebral disc (IVD) to regenerate damaged disc tissue as a potential treatment for low back pain. However, fibrin lacks key extracellular matrix (ECM) components, such as collagen (Col) and hyaluronan (HA), normally found in native nucleus pulposus (NP) tissue. The overall aim of this work was to create a fibrin-based hydrogel, by incorporating Col and HA into the matrix to enhance NP-like matrix accumulation using articular chondrocytes (CC). Firstly, we assessed the effect of fibrin concentrations on hydrogel stability, and the viability and proliferation kinetics of articular chondrocytes. Secondly, we investigated the effect of incorporating Col and HA to enhance NP-like matrix accumulation, and finally, examined the influence of various HA concentrations. Results showed that increasing fibrin concentration enhanced cell viability and proliferation. Interestingly, incorporation of HA promoted sGAG accumulation and tended to suppress collagen formation at higher concentrations. Taken together, these results suggest that incorporation of ECM components can enhance the bioactivity of fibrin-based hydrogels, which may help advance the clinical potential of commercial cell and biomaterial ventures in the treatment of IVD regeneration.